A THEORETICAL AND AXIOLOGICAL EVALUATION OF THE DETENTION OF INDIVIDUALS WITH PSYCHOTIC MENTAL DISORDERS UNDER KUHAP (THE INDONESIAN CRIMINAL PROCEDURE CODE): FROM PROCEDURAL INSTRUMENT TO DISGUISED PUNISHMENT - Fathur Rozzi; Y.A. Triana Ohoiwutun; Fanny Tanuwijaya; Jimmy Z. Usfunan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Detention under the Indonesian Criminal Procedure Code (KUHAP) is intended to function as a temporary, non-punitive procedural instrument to ensure the proper administration of criminal proceedings. However, the application of detention to individuals with psychotic mental disorders reveals a structural inconsistency between substantive criminal law and criminal procedure, causing detention practices to shift into a form of disguised punishment. This article adopts a normative-analytical approach to assess conceptual gaps within KUHAP, examine the implications of procedural incapacity, and evaluate the urgency of implementing medically rehabilitative detention grounded in international human rights principles. The study analyzes legal literature, national regulations, and forensic perspectives to trace the consequences of conventional detention practices for individuals with psychotic mental disorders. The findings indicate that standard detention not only fails to protect their rights but also heightens psychosocial risks, exacerbates mental conditions, and produces substantive injustice. This research underscores the need to reformulate KUHAP by recognizing procedural incapacity, implementing non-punitive detention based on medical rehabilitation, and integrating the principles of legal utility, substantive justice, and human rights protection. Such an approach is expected to bridge the gap between substantive criminal law and criminal procedure while affirming that the protection of the rights of individuals with psychotic mental disorders is not merely a domestic obligation but also a commitment to international human rights standards.